PoTS: Proof of Tunnel Signature for Certificate Based on Blockchain Technology - Dewi Immaniar; Nur Azizah; Dedeh Supriyanti; Nanda Septiani; Marviola Hardini (International Institute for Advanced Science & Technology (IIAST), 2021)
Proof of Tunnel Signature (PoTS) is designed to avoid the main problems found in certificates based on Blockchain technology. In this case, it is so closely related to Cybersecurity. A lightweight protocol such as a Certificate Authenticated Key Agreement (CAKA) is needed to reduce the vulnerability of a system's operation, namely overcoming management overhead by using a decentralized system according to the characteristics of Blockchain Technology. PoTS is the second stage after determining the Key Agreement (KA) or certificate hash in authenticating a node, and this is also a significant step in minimizing computation costs. The nodes generated after the signing process remain anonymous and can be verified optimally. Smart contracts are also used as a support so that this research can ensure transparency and openness of transaction nodes to maintain and improve the efficiency of transaction security for a certificate based on Blockchain Technology.